RECURRENT UTIs IN NON-PREGNANT WOMEN: NON-ANTIBIOTIC PREVENTION AND AN OUTPATIENT STEWARDSHIP ALGORITHM - Zuzanna Jabłońska; Maja Jabłońska; Julia Kamińska; Ewa Jagodzińska; Joanna Zygadło; Wiktor Milewczyk (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Recurrent urinary tract infections (rUTIs) in non-pregnant women represent a major clinical and socioeconomic burden, increasingly complicated by antimicrobial resistance and limited antibiotic options. Aim of the Study: This narrative review synthesizes current evidence on non-antibiotic prevention strategies and proposes a structured outpatient stewardship algorithm. Methodology: A comprehensive literature search across PubMed, Scopus, Web of Science, and Cochrane Library (inception–September 2025) identified studies on behavioral, pharmacological, and immunological prophylaxis in adult women with recurrent uncomplicated UTIs. Results: Evidence supports lifestyle optimization—adequate hydration, postcoital voiding, and intimate hygiene—as safe but variably effective measures. Cranberry-derived proanthocyanidins and D-mannose demonstrate moderate efficacy in reducing recurrences, while vaginal estrogen significantly benefits postmenopausal women by restoring mucosal integrity. Immunostimulants such as OM-89 and methenamine hippurate emerge as promising antibiotic-sparing options, supported by high-quality randomized trials. The proposed outpatient algorithm prioritizes elimination of modifiable risk factors, sequential non-antibiotic prophylaxis, and restricted antibiotic use guided by urine culture results. Non-antibiotic strategies have shown favorable cost-effectiveness and reduced healthcare utilization compared with continuous antibiotic prophylaxis. Future research should standardize outcome definitions, incorporate microbiome and immunological analyses, and evaluate long-term cost–benefit profiles through multicenter pragmatic trials. Conclusions: Integrating non-antibiotic prevention into structured stewardship frameworks offers a sustainable, patient-centered model for rUTI management, mitigating resistance development while maintaining clinical efficacy.